Establishment of transgenic potato cultivar IPB CP1 plants containing gene encoding for superoxide dismutase to increase the abiotic stress tolerance - Musawira Musawira; Suharsono Suharsono; Miftahudin Miftahudin; Aris Tjahjoleksono (Indonesian Journal of Biotechnology, 2022)
Potato ( Solanum tuberosum L.) cultivar IPB CP1 is suitable as a raw material for the potato chip industry. Potato plants are sensitive to various abiotic stresses such as drought, aluminium and salinity, which induce reactive oxygen species (ROS). ROS is very toxic to plant cells. Superoxide dismutase (SOD) is one of the enzymes that catalyse ROS to H2O2 and O2. This study aimed to establish transgenic potato cv. IPB CP1 plants containing the MmCuZn‐SOD gene that are tolerant to various abiotic stresses. Genetic transformation using internodes without buds as explants produced putative transgenic potato with a transformation efficiency of 51.25% and a regeneration efficiency of 38.87%. Integration analysis of the MmCuZn‐SOD transgene in putative transgenic plants by polymerase chain reaction (PCR) with a set of specific primers showed that eight plants contained the MmCuZn‐SOD gene under the control of the 35S CaMV promoter. In vitro salinity stress, aluminium stress, and drought stress assays showed that transgenic plants had a higher number of roots and total root length than non‐transgenic ones. These results indicate that transgenic potato cv. IPB CP1 plants are more tolerant to abiotic stresses than non‐transgenic ones.